Comentario al «motu proprio» del papa Francisco acerca de los límites y modos de la administración ordinaria de los bienes temporales de la Santa Sede - García-Nieto-Barón, María (Estudios eclesiásticos, 2024)
With this commentary, we aim to reflect on the most relevant issues of the motu proprio regarding the limits and modes of the ordinary administration of the temporal goods of the Holy See, dated January 16, 2024. This regulation falls within the context of the reform of the Roman Curia and the economic reform that Pope Francis is implementing during his pontificate. It establishes objective criteria that define the acts of extraordinary administration for entities dependent on the Council for the Economy. The new regulation seeks to protect the principle of subsidiarity, as well as to promote flexibility, dynamism, and transparency in the management of these goods. This is a brief but significant regulation that introduces innovative aspects in the canonical field, such as positive administrative silence.